Paradigma Gerakan Ganda Fazlur Rahman dalam Pembaruan Cara Berpikir Islam Kontemporer (Pusat Riset dan Inovasi Nasional, 2026)
This study examines Fazlur Rahman’s double movement paradigm as a methodological framework for renewing contemporary Islamic thought. The background of this research lies in the ongoing crisis of Islamic epistemology, marked by the dominance of textual-literal interpretations that are detached from historical context, as well as modernist approaches that often lack strong Islamic methodological foundations. This condition has weakened the ability of Islamic thought to respond to modern social, ethical, and intellectual challenges. This research employs a qualitative approach using library research. The primary data consist of Fazlur Rahman’s major works, including Islam, Major Themes of the Qur’an, and Islam and Modernity, while secondary data are drawn from academic journals, books, theses, and previous studies discussing his thought. Data were analyzed through content analysis and interpretative analysis to identify key concepts, methodological patterns, and their implications for contemporary Islamic thought. The findings show that Fazlur Rahman conceptualizes the Qur’an as a source of universal moral values rather than a static legal code. His double movement method emphasizes understanding the Qur’anic text within its historical context and reapplying its moral principles to contemporary realities. This approach positions Rahman within the framework of Islamic neo-modernism, bridging classical Islamic tradition and modern intellectual demands. The study concludes that the double movement paradigm offers a relevant epistemological foundation for renewing Islamic thought, particularly in Qur’anic interpretation, Islamic law, and Islamic education, by promoting contextual, ethical, and critical reasoning.